Analysis of Science Learning Problems in Elementary Schools - Iwan Usma Wardani; Ida Bagus Putu Arnyana; Nyoman Dantes (Jurnal Penelitian Pendidikan IPA, 2023)
Problems are deviations between goals and results. In learning problems influenced by internal and external factors of students. This research method is descriptive qualitative approach. define and analyze narratively. Data through scientific studies reviewed and systematically analyzed. The results show that student problems, namely external factors, come from the family environment. that family Good will give birth to Student Which own character as well as motivation high learning. The school environment has a major role. Teacher as determinant achievement success student. Effort Teacher in increase interest in learning and student achievement including; methods, models, and agar media objective Study can achieved with optimal. Environment public own role form Student character in accordance with culture the people.